The Determinants of Economic Growth in Turkey: 1980-2010 - Hamad, Karwan Khalid (2012)
Many factors affect economic growth, some factors increasing economic growth and others decreasing economic growth. Economic growth is usually measured by the percentage rate of increase in gross domestic production (GDP). The study focuses on investigating determinants of economic growth in Turkey. The study used annual time series data from 1980-2010. This study used the variables; foreign direct investment (FDI), export (EXP), inflation (INF) and government debt (GD) are used as determinants of economic growth in Turkey. The test for the unit roots has been performed by employing the Augmented Dickey Fuller (ADF) test. Long run and short run estimation have been investigated by using Johansen Cointegration and Error Correction approach. The findings of the study reveal that in the long run economic growth in Turkey is positively influenced by FDI and EXP. These variables have significant positive impact on GDP in the long run. If FDI and EXP are increased by USD1 million, GDP is increased by USD942.29 million and USD247.19 respectively. INF has a positive impact on GDP. When INF is increased by one percent, GDP will increase by USD83495.44 million. Although, this result is contradictory with the theories and many evidences, but it is still supported by Datta and Mukhopadhyay (2011). On the other hand, the GD is statistically significant and has a negative effect on GDP. In the short run, lag one of GDP, EXP and GD are among all those independent variables that have short run impact on GDP. Even though FDI and INF are statistically significant in the long run, but in the short run, they are not significant variables.